Algorithmic Exploitation: Understanding Labor Process and Control among RideHailing Platform Workers - M. Falikul Isbah (Jurnal Sosioteknologi, 2022)
This study analyzes the labor process of ride-hailing workers and the platformcompany’s control over them. This research employs Labour Process Theory (LPT)to examine the labor process and control critically. Based on in-depth interviewswith motorcycle drivers working for Go-Jek and Grab between June 2020 and June2021 in Yogyakarta, Kediri, and Jakarta, this research found that labor or workersare transformed into a commodity where job supply and demand are confounded andmediated by digital platforms. Algorithmic management, utilized in this industry, playsa significant role in this digital industry, including its use as a point of production and asa mechanism of control and monitoring in the workplace. The use of feedback systems,ratings, and platform ratings as a consequence of emotional work is used by managersto help monitor their employees. Furthermore, this study reveals that the form of controlconducted by the platform represents an unequal power relation, which producesdissatisfaction and conflicts. We argue that the labor process in this job resembles whatwe coined “algorithmic exploitation,” which means that the platform companies aredeliberately using technology and obscuring the control process over the operations ofthe workers to instill the high standards of service, while the workers are trapped in avery weak employment status as “partners.”